Serum biochemical indices in captive rhesus macaques (Macaca mulatta) - M. Palanivelrajan; M.G. Jayathangaraj; R. Sridhar; M. Parthiban; R. Thirumurugan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Serum bio-chemical parameter study was conducted to file the reference values for Rhesus macaques (Macaca mulatta) reared under captivity. The animals were chemically restrained with ketamine hydrochloride and xylazine hydrochloride and six blood samples (3males and 3 females) were collected from the saphenous vein and processed. In this study, the estimated mean ± S.E. of values of serum biochemical profiles were close to the normal range which was reported earlier. But, the total protein and Alanine aminotransferase levels were less and serum level of phosphorus was comparatively high.